The β-chemokines MIP-1α and RANTES and lipoprotein metabolism in HIV-infected Brazilian patients - Mikawa, Angela Yumico [UNESP]; Malavazi, Iran [UNESP]; Tagliavini, Sandra Antonia [UNESP]; Abrão, Emiliana P. [UNESP]; Costa, Paulo Inácio da [UNESP] (FapUNIFESP (SciELO), 2005)
HIV patients are predisposed to the development of hypertriglyceridemia and hypercholesterolemia as a result of both viral infection and HIV infection therapy, especially the protease inhibitors. Chemokines and cytokines are present at sites of inflammation and can influence the nature of the inflammatory response in atherosclerosis. We investigated the correlation between biochemical variables and β-chemokines (MIP-1α and RANTES) and the apolipoprotein E genotype in HIV-infected individuals. The apolipoproteins were measured by nephelometry. Triglycerides and total cholesterol were determined by standard enzymatic procedures. The β-chemokines were detected by ELISA. The genetic category of CCR5 and apolipoprotein E were determined by PCR amplification and restriction enzymes. Immunological and virological profiles were assessed by TCD4 + and TCD8 + lymphocyte counts and viral load quantification. Positive correlations were found between apo E and CD8 + (p = 0.035), apo E and viral load (p = 0.018), MIP-1α and triglycerides (p = 0.039) and MIP-1α and VLDL (p = 0.040). Negative correlations were found between viral load and CD4 + (p = 0.05) and RANTES and CD4 + (p = 0.029). The β-chemokine levels may influence lipid metabolism in HIV-infected individuals. © 2005 by The Brazilian Journal of Infectious Diseases and Contexto Publishing. All rights reserved.
Keywords: β-chemokine; Cholesterol; Genotype; HIV; Lipoproteins; Triglyceride; apolipoprotein E; beta chemokine; CD4 antigen; CD8 antigen; chemokine receptor CCR5; cholesterol; macrophage inflammatory protein 1alpha; RANTES; triacylglycerol; very low density lipoprotein; adult; Brazil; chemical analysis; cholesterol blood level; clinical article; controlled study; correlation analysis; enzyme analysis; enzyme linked immunosorbent assay; female; gene amplification; genetic analysis; genotype; human; Human immunodeficiency virus infection; individuality; lipoprotein metabolism; lymphocyte count; male; nephelometry; polymerase chain reaction; restriction mapping; triacylglycerol blood level; virus load; Adult; Apolipoproteins E; Biological Markers; CD4-CD8 Ratio; Female; HIV Infections; Humans; Macrophage Inflammatory Protein-1; Male; Receptors, CCR5; Viral Load